Activation of the Nrf2/ARE signaling pathway protects against palmitic acid-induced renal tubular epithelial cell injury by ameliorating mitochondrial reactive oxygen species-mediated mitochondrial dysfunction - Jiang, Xu-shun; Cai, Meng-yao; Li, Xun-jia; Zhong, Qing; Li, Man-li; Xia, Yun-feng; Shen, Qing; Du, Xiao-gang; Gan, Hua (Frontiers in Medicine, 2022)
Chronic kidney disease (CKD) is often accompanied by dyslipidaemia, and abnormal lipid metabolism in proximal tubule cells is considered closely related to the dysfunction of proximal tubule cells and eventually leads to accelerated kidney damage. Nuclear factor E2-related factor 2 (Nrf2), known as a redox-sensitive transcription factor, is responsible for regulating cellular redox homeostasis. However, the exact role of Nrf2 in dyslipidaemia-induced dysfunction of proximal tubule cells is still not fully elucidated. In the present study, we showed that palmitic acid (PA) induced mitochondrial damage, excessive mitochondrial reactive oxygen species (ROS) (mtROS) generation, and cell injury in HK-2 cells. We further found that mtROS generation was involved in PA-induced mitochondrial dysfunction, cytoskeletal damage, and cell apoptosis in HK-2 cells. In addition, we demonstrated that the Nrf2/ARE signalling pathway was activated in PA-induced HK-2 cells and that silencing Nrf2 dramatically aggravated PA-induced mtROS production, mitochondrial damage, cytoskeletal damage and cell apoptosis in HK-2 cells. However, the mitochondrial antioxidant MitoTEMPOL effectively eliminated these negative effects of Nrf2 silencing in HK-2 cells under PA stimulation. Moreover, activation of the Nrf2/ARE signalling pathway with tBHQ attenuated renal injury, significantly reduced mtROS generation, and improved mitochondrial function in rats with HFD-induced obesity. Taken together, these results suggest that the Nrf2/ARE-mediated antioxidant response plays a protective role in hyperlipidaemia-induced renal injury by ameliorating mtROS-mediated mitochondrial dysfunction and that enhancing Nrf2 antioxidant signalling provides a potential therapeutic strategy for kidney injury in CKD with hyperlipidaemia.